Literature Review on the Herbo Mineral Preparation Kravyada Rasa. - Manju, Raj K; Sanila, V K (International Research Journal of Ayurveda & Yoga, 2023)
Science of Ayurveda was introduced with the Branch of Rasasastra from 3rd century onwards. Rasasastra is a pharmaceutical branch of Indian Systems of medicine which mainly deals with Metals, Minerals, Animal origin products, Toxic herbs and their use in therapeutics. These rasa dravyas are found to have instant effectiveness, minimal dose and extensive therapeutic utility irrespective of constitutional variation. After the development of Rasasastra, inclusion of many herbo mineral preparations can be noticed in the Ayurveda books. Kravyada rasa is one such formulation seen in latest books of Ayuveda with a unique blend of herbal and mineral drugs which is fortified by subjecting to bhaavana (levigation.) in different media. Kravyada rasa is indicated in context of Agni mandhya or Mandaagni or Ajeerna adhikara. The formulation includes Parada, Gandhaka,Loha bhasma, Tamra bhasma,Tankana, Vida lavana and Maricha subjected to levigation. in Jambira juice ,Panchakola kwatha,Amlavetasa and Chanakamla. Formulation is also unique in its preparation as Kajjali along with Tamra bhasma and Loha bhasma is made into Parpati (thin flake like) and then subjected to repeated levigation. after adding remaining ingredients. In this study an attempt is made to gather information on Kravyada rasa from various classics with insight into ingredients, dosage and mode of action, thereby enabling further studies on Kravyada rasa; a less exploited herbomineral formulation.